Development of a Literacy House to Increase Interest in Reading in Children - Syaeful Bakhri; Anisa Suhada Putri (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2023)
Interest is a combination of desire and will that can develop if there is motivation. If interest and motivation are absent, habits generally don't grow and don't develop. The habit of reading must be applied from an early age, in order to overcome the problem of a lack of interest in reading in children. The creation of a